How and What Effect of English Songs on Preschool Students - Fidzikri, Fala Tania; Salsabilla, Salwa; Nandini, Nadya Putri; Susilawati, Susilawati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This study analyzes how english songs give impact to preschoolers in learning English. Investigates the effectiveness of using English songs to teach English as a foreign language (EFL) to preschool students based on the theory. The research shows that music enhances grammar, pronunciation, and vocabulary while creating a fun and engaging environment. These dynamic experiences attract and retain attention, increasing motivation and fostering positive associations with language learning. Early childhood (2-6 years old) is a very important period in language acquisition. English songs, with their catchy melodies and rhythmic structures, can be a fun and engaging way for preschoolers to learn English. This research uses qualitative methods, specifically descriptive analysis. The data in the form of English songs will describe what influence they have on preschoolers' English language skills.